2018
DOI: 10.3389/fendo.2018.00702
|View full text |Cite
|
Sign up to set email alerts
|

Brain SIRT1 Mediates Metabolic Homeostasis and Neuroprotection

Abstract: Sirtuins are evolutionarily conserved proteins that use nicotinamide adenine dinucleotide (NAD+) as a co-substrate in their enzymatic reactions. There are seven proteins (SIRT1-7) in the human sirtuin family, among which SIRT1 is the most conserved and characterized. SIRT1 in the brain, in particular, within the hypothalamus, plays crucial roles in regulating systemic energy homeostasis and circadian rhythm. Apart from this, SIRT1 has also been found to mediate beneficial effects in neurological diseases. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 141 publications
1
82
0
3
Order By: Relevance
“…In this regard, proteins that modulate histone acetylation pattern could be responsible of many of these neuroprotective effects. SIRT1 has received a great deal of attention, believed to be a modulator of several neuroprotective effects in different therapies and having an important role in memory regulation as well as in other cognitive abilities [25,57]. A marked reduction in hippocampal SIRT1 levels has been described during aging and different neuroprotective strategies (including treatment with different polyphenolic compounds) have been reported to revert this reduction, pointing out this protein as a mediator of their neuroprotective effects [6,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, proteins that modulate histone acetylation pattern could be responsible of many of these neuroprotective effects. SIRT1 has received a great deal of attention, believed to be a modulator of several neuroprotective effects in different therapies and having an important role in memory regulation as well as in other cognitive abilities [25,57]. A marked reduction in hippocampal SIRT1 levels has been described during aging and different neuroprotective strategies (including treatment with different polyphenolic compounds) have been reported to revert this reduction, pointing out this protein as a mediator of their neuroprotective effects [6,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 regulates metabolic homeostasis and neuronal aging [ 4 ]. It may also have neuroprotective effects and have a beneficial effect on neurodegenerative diseases such as Parkinson’s and Alzheimer’s diseases [ 5 , 6 , 7 ]. Citicoline raises the level and increases SIRT1 activity in the rat brain, cultured neurons, and in peripheral blood mononuclear cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…SIRT-1 regulates a wide variety of biological functions, including embryonic development, cell differentiation and apoptosis (Borra et al, 2005;Wang et al, 2018a). In AD, the accumulation of Aβ decreases the levels of SIRT-1 in neurons (Donmez and Outeiro, 2013;Jęśko et al, 2017;Xu et al, 2018). In this line, some studies reported that the preventive action of RV is probably related to the modulation of SIRT-1 expression and activity in neurons (Lagouge et al, 2006;Feng et al, 2013).…”
Section: Neuroprotective Effects Of Resveratrol In Alzheimer's Diseasementioning
confidence: 99%